A sliding-mode controller for directional control of articulated heavy vehicles. (February 2014) - Tabatabaei Oreh, S Hamed; Kazemi, Reza; Azadi, Shahram
In order to improve the handling and stability of a tractor–semitrailer, a new sliding-mode controller is designed on the basis of a non-linear three-degree-of-freedom model of the vehicle. Three state variables, namely the tractor's yaw rate, the tractor's lateral velocity and the articulation angle, are controlled as the target responses using active steering. A new version of the desired articulation angle is proposed so that the rear end of the semitrailer unit is forced to follow the path of the fifth wheel if the proposed reference value is tracked. A 12-degree-of-freedom non-linear model of the articulated heavy vehicle validated by real test data is used to evaluate the control system. The comparative simulation results prove the significant effects of the proposed non-linear control method with respect to a previously designed linear controller on improving the handling and stability performance, especially under severe driving conditions.